Exurban land use and landowner perceptions of ecosystem management concepts - Shinderman, Matthew J., author; Woodmansee, Robert G., advisor; Vaske, Jerry, committee member; Williams Daniel R., committee member; Mitchell, John E., committee member (Colorado State University. Libraries, 2004)
The Rocky Mountain West, USA, is currently experiencing dramatic population growth. The region has consistently grown at a greater rate than the nation as a whole, especially in counties containing federal recreation lands. Of particular concern is increasing growth in exurban areas adjacent to public lands. Information concerning land uses associated with these demographic changes is becoming more available, but little is known about the potential impacts these changes will have on regional conservation efforts. Mail surveys were sent to large lot (25-50 acres) landowners from six counties within the southern Rocky Mountain region. Surveys were designed to document land uses and landowner perspectives of ecosystem management concepts. Based on the results, guidelines for incorporating exurban landowners into ecosystem management plans were proposed. The study presented here is divided into three distinct sections. For this dissertation, each section is treated independently as a separate study, each with its own chapters. As a result there is some repetition in the reporting of methods and background material among the three papers. In the first paper, salient exurban land uses and landowner demographics are summarized. Exurban landowners practice several land uses that have the potential to significantly influence ecosystem management, including grazing, weed management, timber management, and private access to public lands. The second paper addresses the degree to which exurban landowners would be willing to participate in ecosystem management as measured by landowner attitudes and willingness to vote for hypothetical management activities. The majority of landowners surveyed expressed support for ecosystem management under the condition that managers address property rights and privacy concerns. Finally, the third paper presents a summary of studies conducted on private landowner support for ecosystem management. Based on this information, several guidelines are proposed that will better enable managers to include exurban landowners in ecosystem management plans.
Keywords: forestry; environmental science